(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Grain filling determines the grain weight, a major component of grain yield in cereals. Grain filling in barley depends on current assimilation and culm reserves (mainly water-soluble carbohydrates). Nowadays barley is facing heat stress problem which is mostly responsible to reduce the yield of barley. A field experiment was conducted at the Field Lab, Department of Crop Botany, BangladeshAgriculturalUniversity, Mymensingh during November 2015 to March 2016 to study the grain filling patterns and the contributions of culm reserves to grain yield under heat stress. The experiment consisted of two factors—barley cultivars and heat stress. The heat stress was imposed by late sowing. The tillers were sampled once a week during grain filling period to determine the changes in dry weights of different parts, viz., leaves, culm with sheath, spikes, and grains; and to examine the contribution of culm reserves to grain yield. The results in the experiment revealed that the grain yield was reduced by 22-28% due to the stress. The grain yield varied from 52 to 150 g m−2 with the mean of 102 g m−2 under control while it varied from 37 to 116 g m−2 with the mean of 75 g m−2 under heat stress. Among the cultivars studied BARI Barley5, BARI Barley2 and BARI Barley1, seemed as high yielders while BARI Barley3, BARI Barley4, BARI Barley6 as the low yielders under heat stress treatment. The reduction in grain yield was attributable mainly to lighter grain weight due to the stress. Heat stress drastically reduced the grain filling duration by 45–50%. However, the stress increased the grain filling rate by 6–53%. The amount of reserves remobilized to grain varied among the cultivars ranging from 4.8 to 12.77 mg spike−1 in control and from 1.73 to 6.25 mg spike−1 in stressed plants. The stressed barley plants exhibited lower accumulation of reserves in culm but they showed almost its complete remobilization to the grain. The contribution of culm reserves to grain yield varied from 1.13 to 19.52%, and 1.09 to 2.11% in control and in stressed plants, respectively. In conclusion, culm reserve is the important attributes in grain yield in Bangladeshi barley cultivars but the contribution remains almost unaffected due the post-anthesis heat stress. J. Bangladesh Agril. Univ. 15(2): 174-181, December 2017